Echocardiographic Monitoring of Anatomical Changes in the Myocardium of Pediatric Patients with a Diagnosis of Non-Compaction Cardiomyopathy. 2017 – 2021: Seguimiento Ecocardiográfico De Cambios Anatómicos Del Miocardio De Pacientes Pediátricos con Diagnóstico De Miocardiopatía No Compactada. 2017 – 2021 - Loo-Valverde, María (2024)
Background:   Non-compaction cardiomyopathy (NCM) is known as the lack of maturation of the myocardium that is evidenced by prominent trabeculations and the presence of recesses in newborns and infants that can manifest clinically as heart failure. The purpose of the research is to evaluate the anatomical development of pediatric patients diagnosed with NCM at an early age. Clinical Case: Retrospective case series study of patients diagnosed with non-compaction cardiomyopathy during the first year of life, confirmed according to Jenni criteria, with echocardiographic follow-up every 6 months, from 2017 - 2021. The patients were diagnosed in the first months of life. life, 3 had associated heart disease, 3 had arrhythmias, 3 died and 1 abandoned the controls at 2 months of age. In the 3 patients who remained, it was evident that the ratio of non-compacted myocardium (NC) / compacted myocardium (C) only remained high in 1 patient. The ejection fraction (EF) improved in all patients, the number of trabeculae only decreased in one patient. Conclusions: Anatomical changes in patients diagnosed with non-compaction cardiomyopathy can evolve to myocardial maturation and improvement in ventricular function.